Estudo da viabilidade da produção de etanol a partir de suco de caju (Anacardium occidentale L.) utilizando células imobilizadas em bagaço de caju - Pacheco, Alexandre Monteiro (2009)
The use of cashew apple peduncle, a vast available material found in Ceará that is usually wasted, combined with production of ethanol, is the focus of this project. Cashew apple juice, rich in fructose, glucose, salts and vitamins, is an appropriate raw material for alcoholic fermentation by the yeast Saccharomyces cerevisiae. The search for improvements in ethanol production in this work was achieved through the study of the use of yeast immobilized in cashew apple bagasse support, (SBC). Cell immobilization has been studied by many researchers and has been an important technique because of the possible benefits and advantages as the increase in productivity. Cashew apple bagasse is a cheap and easily accessible raw material to the application of the immobilization technique. As comparison, results with free, immobilized cells in calcium alginate, a known agent for immobilization by encapsulation, and immobilized cells by adsorption on SBC were studied. Preliminary fermentation assays using immobilized cells on SBC were performed, as well as consecutive and storage fermentations. The following kinetic parameters were checked: productivity (Qp, gL-1h-1), efficiency (Ef,%), substrate / biomass yield (Yx / s, g.g-1) and substrate / product yield (Yp / s, g.g - 1). SBC presented advantages, such as high cell densities and adhesion, generating high yields (≈ 5 g.L-1h-1). With respect to efficiency and rate of substrate / product yield, immobilized cells reached values similar to those obtained with free cells in the integral cashew apple juice (about 90% and 0.47 respectively). Another advantage is the durability and possibility of reuse of SBC making the process more economical, fast and efficient. SBC was reused for at least 10 consecutive batches and remained stable, at refrigerator, for 6 months